GPR75 mediates hyperuricemia-induced endothelial inflammatory injury via a HOTAIR/miR-141-3p regulatory network - Jiawu Fu; Junbing He; Keshen Li; Manting Zhang; Jiekai Li; Yuchun Liu; Yusen Chen; Wei Bi (Molecular Biology Reports, 2026)

Biomass-derived porous carbon supported Cu₃P/TiO₂ N-doped heterojunction for visible-light photocatalysis - Tingxuan Xie; Manting Zheng; Qingdong Deng; Weixi Zhang; Shenyi Liang; Wei Li; Yinli Dai; Jiaqi Zhang; Xu Feng; Zhanlin Wang; Junhao Li; Runjing Li; et al. (Colloids and Surfaces C: Environmental Aspects, 2026)

PSE-like chicken protein isolate/carboxymethyl chitosan particles for curcumin-loaded Pickering emulsions: Encapsulation efficiency and gastrointestinal fate - Chenyan Zhu; Dianbo Zhao; Mengge Li; Junguang Li; Yuntao Wang; Manting Du; Wuchao Ma; Ke Li; Yanhong Bai (Food Research International, 2026)

Developmental and behavioral toxicity of citalopram in zebrafish early life stages: Neurochemical alterations, oxidative stress responses, and transcriptomic signatures - Yanhua Liu; Manting Li; Jianqiu Yu; Fanrui Yu; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2026)

Time evolution of infection state correlation of nodes in an SIR model on a random contact network - Meili Li; Haodong Shi; Junling Ma; Manting Wang (Mathematical Biosciences, 2026)

Genome-wide identification and single-cell transcriptomic analysis of the mcm gene family in zebrafish reveals its role in TCDD-induced reproductive toxicity - Wenbo Jiang; Xinyi Li; Yubo Zhao; Xinyue Yang; Manting Jin; Jiayu Li; Jiayang Zhao; Ying Huang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

BOTDR Monitoring of Tensile State in Three-Core Fiber-Optic Composite Submarine Cables with a Three-Layer Mechanical Structure and Dual-Threshold Sensing Model - Manting Guo; Yanpeng Hao; Yashuang Zheng; Busheng Chen; Xin Yu; Licheng Li (Journal of Marine Science and Engineering, 2026)
Submarine cables are critical components for power transmission in offshore wind farms, making their condition monitoring paramount for ensuring operational reliability. Addressing unclear strain transfer and underdeveloped Brillouin optical time-domain reflectometry (BOTDR) sensing models for three-core fiber-optic composite submarine cables, this study investigated a 66 kV cable and clarified a BOTDR monitoring principle based on the three-layer mechanical structure. Using the external optical unit’s average Brillouin shift for temperature compensation, four characteristic parameters (Δvy, Δvp, vm, vF) were analyzed. The results show the optical unit’s tensile strain-induced Brillouin shift exhibits periodic distribution along the cable. The stable average peak vF achieved a correlation coefficient of 0.98 with tensile load Fi. A dual-threshold sensing model was established: no shift response below F0 = 90 kN (7.84% Rated Tensile Strength (RTS)); strong linear correlation between vF and Fi beyond Fm = 110 kN (9.58% RTS) with a tensile sensitivity coefficient of 0.03788 MHz/kN. This study provides key BOTDR technical support for submarine cable tensile monitoring in complex marine environments.

Germination-driven dynamic changes of phenolic compounds in oats and the underlying mechanisms for antioxidation enhancement - Manting Huang; Qiaochun Chen; Siqian Li; Jiayi He; Yuting Su; Mingfu Wang (Food Chemistry, 2025)

Neurodevelopmental toxicity of black carbon in zebrafish: behavioral and metabolomic insights - Fanrui Yu; Yanhua Liu; Manting Li; Yaqian Gao; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2025)

Self-assembly of tea polyphenol onto the high strength chitosan film fabricated via a new way to enhance the antioxidant and antibacterial activity for meat preservation - Yuntao Wang; Xiuqin Guo; Zhilong Qin; Rongqin Liu; Shengjie Li; Manting Du; Si Qiu; Yanhong Bai (Food Packaging and Shelf Life, 2025)

Harnessing β-glucan conjugated quercetin nanocomplex to function as a promising anti-inflammatory agent via macrophage-targeted delivery - Yuting Su; Manting Huang; Qiaochun Chen; Jiayi He; Siqian Li; Mingfu Wang (Carbohydrate Polymers, 2025)

Tuning quantum dots emission on DNA tetrahedron/silica nanosphere/graphene oxide nanointerface for ratiometric fluorescence assay of Pb2+ in multiplex samples - Manting Li; Haikun Luo; Zhao Wang; Qian Mo; Shanshan Zhong; Yu-ang Mao; Shuting Li; Xinchun Li (Analytica Chimica Acta, 2024)

Enhancing the bioavailability of quercetin via the construction of carboxymethylated curdlan/quercetin nanocomplex - Yuting Su; Qian Zhou; Hui Xu; Manting Huang; Siqian Li; Jiayi He; Ka-Wing Cheng; Mingfu Wang (Food Hydrocolloids, 2024)

Optimization of water quality evaluation index using information sensitivity method and variable fuzzy model for the Guo River, China - Shuoya Cheng; Peigui Liu; Mei Yao; Mei Li; Meng Liu; Manting Shang (Environmental Science and Pollution Research, 2024)

Microsatellite-Marker-Based Evaluation of Stock Enhancement for Kuruma Prawn Penaeus japonicus in Beibu Gulf, South China Sea - Mengyi Zhang; Yu Zhao; Binbin Shan; Yan Liu; Changping Yang; Liangming Wang; Manting Liu; Qijian Xie; Yuan Li; Jianwei Zou; Dianrong Sun (Fishes, 2023)
The objectives of this study were to evaluate the effect of stock enhancement on Penaeus japonicus (Bate, 1888) in Beibu Gulf, South China Sea, and to investigate whether stock enhancement has genetically affected the natural population of P. japonicus in the Beibu Gulf waters. Five microsatellite loci were used to identify released individuals among recaptured specimens. In total, 13 of the 487 recaptured individuals were found with their corresponding parents for this release of shrimp seedlings, accounting for 2.67% of the total recaptured P. japonicus. Furthermore, it was determined that the genetic differences among the broodstock, released, and recaptured populations of P. japonicus were small and did not cause significant changes in the genetic structure of P. japonicus in the area. In conclusion, the stock enhancement of P. japonicus in Beibu Gulf had a certain effect on resource restoration, and there is no difference in the genetic characteristics obtained by the microsatellite markers compared to the original population in this area.

Constraining the sources and cycling of dissolved inorganic carbon in an alpine river, eastern Qinghai-Tibet Plateau - Wanfa Wang; Jun Zhong; Si-Liang Li; F. Ulloa-Cedamanos; Sen Xu; Sainan Chen; Manting Lai; Sheng Xu (Science of The Total Environment, 2023)

Trace elements in aquatic products from Shenzhen, China and their implications for human exposure - Manting Rao; Xiangyu Li; Xiaoqiong Xu; Duo Zhang; Jiaojiao Ma; Jiayin Huang; Jiayi Xu; Quanzhi Zheng; Jiajia Ji; Shaoyou Lu (Science of The Total Environment, 2023)

Identifying oxidative stress-related biomarkers in idiopathic pulmonary fibrosis in the context of predictive, preventive, and personalized medicine using integrative omics approaches and machine-learning strategies - Fan Yang; Wendusubilige; Jingwei Kong; Yuhan Zong; Manting Wang; Chuanqing Jing; Zhaotian Ma; Wanyang Li; Renshuang Cao; Shuwen Jing; Jie Gao; Wenxin Li; et al. (EPMA Journal, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Organophosphate ester exposure among Chinese waste incinerator workers: Urinary levels, risk assessment and associations with oxidative stress - Xiaoling Wu; Duo Zhang; Yining Chen; Junchun Shen; Xiangyu Li; Quanzhi Zheng; Jiaojiao Ma; Jiayi Xu; Manting Rao; Xiang Liu; Shaoyou Lu (Science of The Total Environment, 2023)

Responding to environmental pollution-related online posts: behavior of Web surfers and its influencing factors - Yong Liu; Manting Li; Juanjuan Zhao; Haidong Yu (Environment, Development and Sustainability, 2019)